Upaya Meningkatkan Hasil Belajar Matematika Menggunakan Model Pembelajaran Numbered Heads Together (NHT) pada Siswa Kelas V SD Negeri 2 Kalikebo Tahun Pelajaran 2023/2024 - Farida Dwi Safitri; Putri Zudhah Ferryka; Isna Rahmawati (Lembag, 2024)
This research aims to improve the learning outcomes of grade V students of SD Negeri 2 Kalikebo. This study uses the Numbered Heads Together (NHT) learning model in the mathematics subject of fraction multiplication material. This Classroom Action Research (PTK) uses the Kemmis and Taggart model. The subjects of this study were fifth grade students of SD Negeri 2 Kalikebo, totaling 20 students. Data collection techniques through evaluation tests, observation, and documentation. The results showed that: (1) students become more active in learning activities. (2) there was an increase in math learning outcomes in fifth grade students of SD Negeri 2 Kalikebo. The percentage of completeness of learning outcomes during the pre-cycle was 5 students or 25% of 20 students, then cycle I there were 10 students or 50%, and in cycle II there were 16 students or 80% who reached KKTP ≥70.